Control interno de propiedad, planta y equipo en el GAD Municipal de Vinces en el período 2023. - Tapia León, Galo José (2025)
The study analyzes the internal control of Property, Plant and Equipment in the Municipal GAD of Vinces during 2023, identifying deficiencies in the registration, valuation and maintenance of assets. The investigation shows the lack of formal procedures for the depreciation and control of assets, which impacts financial transparency and investment planning. Inconsistencies were detected between the physical and accounting inventory, in addition to the absence of regular audits, increasing the risk of errors and fraud. The lack of a preventive maintenance plan has generated deterioration in essential assets, increasing repair costs and affecting the provision of public services. As solutions, it is recommended to implement a comprehensive asset registration and labeling system, establish clear valuation and depreciation procedures, and design a preventive maintenance plan. These actions will strengthen asset management, guarantee the reliability of financial statements and improve the operational efficiency of the Vinces Municipal GAD.